Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (Orientations in Development, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género